치과심미치료 만족도가 구강건강관련 삶의 질(OHIP-14)에 미치는 영향 - 박은미; 유소연; 장종화 (Han'guk Ch'iwisaeng Hakhoe chi, 2011)
Objectives : It examines influence of satisfaction with dental esthetics upon quality of life related to oral health after examining the satisfaction with dental esthetics and the quality of life related to oral health according to subjective perception. Methods : The subjects who have experience of dental esthetics from June 2010 to August 2010 in 50 places of hospitals and clinics with dental esthetics in Seoul, which were selected with convenience sampling, the structured questionnaire was widely distributed to 315 people who agreed to research. After making the subjects respond with self-reported method, data was collected. 298 copies except 17 copies were used in the final analysis. Results : The better in the perceived general health group led to the higher satisfaction with orthodontic treatment(p=0.001). There was significant difference even in satisfaction with dental bleaching(p=0.030). The better in the perceived general health group led to the higher quality of life related to oral health(p=0.002). The subjective perception was indicated to have relationship with satisfaction at dental esthetics or quality of life related to oral health. The satisfaction with orthodontic treatment(β=2.142, p=0.038) was indicated to be relevant factor of having influence upon quality of life related to oral health. Conclusion : As a result of analyzing partial correlation analysis by having subjective perception as control variable,the satisfaction with orthodontic treatment and the life quality related to oral health showed positive correlation. KCI Citation Count: 15